Metal and organic characterization of bladder stones removed surgically from VesicoVaginal Fistula patients at the National Obstetric Fistula Centre, Abakaliki, Ebonyi State - Okorie UC; Sunday-Adeoye I; Obuna JA; Daniyan ABC; Ekwedigwe KC; Oje AO; Yakubu EN; Chukwu CJ; Uro-Chukwu; Omaka ON (Archive of Urological Research - Peertechz Publications, 2022)
Objectives: Complication of obstetric fistula is the formation of bladder stones which rarely occur in Vagina-Vesico Fistula (VVF) patients. In this study, the metal and organic characterization of bladder stones removed between 2010-2019 from vesicovaginal fistula patients managed at the National Obstetric Fistula Centre (NOFIC), Abakaliki, Ebonyi State, Nigeria were carried out.  Methods: The solubility of the bladder stones in different solvents were investigated and metal compositions were determined using Inductively Coupled Plasma- Optical Emission Spectrometry (ICP-OESS). The qualitative chemical composition was determined following standard procedures while the structural chemical characterization and functional groups were determined using the Gas Chromatography-Mass Spectrometry (GC-MS) and Fourier-Transform Infrared spectroscopy (FTIR).  Results: Distilled water and aqueous solvent chloroform extract of W. lateritia demonstrated significant capacity to dissolve bladder stones in-vitro. Chemical compounds identified include uric acid, oxalate, cysteine, and phosphate from the bladder stones. The metals found in the bladder stones were: Ca, Na, Cu, Zn, Mg, B, Pb, and Al. Trace elements can influence the external morphology of growing crystals and may increase or decrease the speed of the crystallization process. The GC-MS revealed the presence of the following compounds: methyl 2-Hydroxyethyl sulfoxide; methylene chloride; mercaptamine;1,1diethoxy, dichloroactealdehyde; Cyclopentasiloxane; monoammonium salt; di-Allo-Cystathionine; dichloroacetaldehyde; 2-(2Furyl)-2,5-dimethyltetrahydrofuran; Methenamine; 1,1-Difluoro-1-sila-5-thiacyclooctane; Triacetonetriperoxde; 4-Aminosalicylic acid, 3-Trimethylsilyl (3TMS) derivative;Pentanethiol; and 2,5-Bis-(5-hexyl-[1,3,2]dioxaborinan-2-yloxy)-benzene. FTIR revealed the following: hydroxyl, carboxylic, ester, aromatic, and aliphatic groups, confirming the compounds identified.  Conclusion: Metals (Mg, Ca, Pb, etc), organic metabolites (oxalate, cystine, uric acid, phosphate, methenamine, methylene chloride, 4-Aminosalicylic acid, 3-Trimethylsilyl, etc) were found in the bladder stones.